Experimental and numerical investigations of S960 ultra-high strength steel slender welded I-section columns failing by local–flexural interactive buckling - Su, Andi (2022)
The present paper reports experimental and numerical investigations into the local–flexural interactive buckling behaviour and resistance of S960 ultra-high strength steel slender welded I-section columns. A testing programme was firstly conducted and included initial geometric imperfection measurements and ten pin-ended column tests. The pin-ended column test setup, procedures and results were fully reported and analysed. The progression of local buckling and flexural buckling was discussed. Following the testing programme, a numerical modelling programme was conducted, where finite element models were developed to replicate the test structural responses and then employed to perform parametric studies to generate further numerical data. It is worth noting that the current European code and American specification are only applicable to steel structures with material yield strengths up to 700 MPa (or 690 MPa). Regarding the design of slender welded I-section columns failing by local–flexural interactive buckling, both codes adopt the same concept — combined use of effective width method to account for local buckling and buckling curve to account for flexural buckling. The obtained test and numerical data were employed to assess the applicability of the codified design rules to S960 ultra-high strength steel slender welded I-section columns. The assessment results revealed that the European code leads to conservative interactive buckling resistance predictions, mainly due to the use of conservative buckling curve, while the American specification yields a good level of design accuracy and consistency. Finally, a revised Eurocode design approach was proposed and shown to result in more accurate and consistent interactive buckling resistance predictions for S960 ultra-high strength steel slender welded I-section columns.